The man, the plant, and the insect: shooting host specificity determinants in Serratia marcescens pangenome - Shikov, Anton E.; Merkushova, Anastasiya V.; Savina, Iuliia A.; Nizhnikov, Anton A.; Antonets, Kirill S. (Frontiers in Microbiology, 2023)
Serratia marcescens is most commonly known as an opportunistic pathogen causing nosocomial infections. It, however, was shown to infect a wide range of hosts apart from vertebrates such as insects or plants as well, being either pathogenic or growth-promoting for the latter. Despite being extensively studied in terms of virulence mechanisms during human infections, there has been little evidence of which factors determine S. marcescens host specificity. On that account, we analyzed S. marcescens pangenome to reveal possible specificity factors. We selected 73 high-quality genome assemblies of complete level and reconstructed the respective pangenome and reference phylogeny based on core genes alignment. To find an optimal pipeline, we tested current pangenomic tools and obtained several phylogenetic inferences. The pangenome was rich in its accessory component and was considered open according to the Heaps' law. We then applied the pangenome-wide associating method (pan-GWAS) and predicted positively associated gene clusters attributed to three host groups, namely, humans, insects, and plants. According to the results, significant factors relating to human infections included transcriptional regulators, lipoproteins, ABC transporters, and membrane proteins. Host preference towards insects, in its turn, was associated with diverse enzymes, such as hydrolases, isochorismatase, and N-acetyltransferase with the latter possibly exerting a neurotoxic effect. Finally, plant infection may be conducted through type VI secretion systems and modulation of plant cell wall synthesis. Interestingly, factors associated with plants also included putative growth-promoting proteins like enzymes performing xenobiotic degradation and releasing ammonium irons. We also identified overrepresented functional annotations within the sets of specificity factors and found that their functional characteristics fell into separate clusters, thus, implying that host adaptation is represented by diverse functional pathways. Finally, we found that mobile genetic elements bore specificity determinants. In particular, prophages were mainly associated with factors related to humans, while genetic islandswith insects and plants, respectively. To the best of our knowledge, the presented research is the first to identify specific genomic features of S. marcescens assemblies isolated from different hosts at the pangenomic level.